Muscular Strength as a Predictor of All-Cause Mortality in an Apparently Healthy Population: A Systematic Review and Meta-Analysis of Data From Approximately 2 Million Men and Women (2018)
Objectives: The aims of the present systematic review and meta-analysis were to determine the relationship between muscular strength and all-cause mortality risk and to examine the sex-specific impact of muscular strength on all-cause mortality in an apparently healthy population. Data Sources: Two authors systematically searched MEDLINE, EMBASE and SPORTDiscus databases and conducted manual searching of reference lists of selected articles. Study Selection: Eligible cohort studies were those that examined the association of muscular strength with all-cause mortality in an apparently healthy population. The hazard ratio (HR) estimates with 95% confidence interval (CI) were pooled by using random effects meta-analysis models after assessing heterogeneity across studies. Data Extraction: Two authors independently extracted data. Data Synthesis: Thirty-eight studies with 1,907,580 participants were included in the meta-analysis. The included studies had a total of 63,087 deaths. Higher levels of handgrip strength were associated with a reduced risk of all-cause mortality (HR=0.69; 95% CI, 0.64-0.74) compared with lower muscular strength, with a slightly stronger association in women (HR=0.60; 95% CI, 0.51-0.69) than men (HR=0.69; 95% CI, 0.62-0.77) (all P less than .001). Also, adults with higher levels of muscular strength, as assessed by knee extension strength test, had a 14% lower risk of death (HR=0.86: 95% CI, 0.80-0.93; P less than .001) compared with adults with lower muscular strength. Conclusions: Higher levels of upper- and lower-body muscular strength are associated with a lower risk of mortality in adult population, regardless of age and follow-up period. Muscular strength tests can be easily performed to identify people with lower muscular strength and, consequently, with an increased risk of mortality. © 2018 American Congress of Rehabilitation Medicine